Karakteristik Parameter Prototipe Pembangkit Listrik Tenaga Sampah (PLTSa) Menggunakan Peltier - Fatmawati Azis; Sulistianingsih Nur Fitri; Akbar Naro Parawangsa (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2026)
This research aims to design and build a power generation system that utilizes heat from waste combustion using a Peltier thermoelectric module, test the effectiveness of converting heat energy into electricity, and analyze the effect of fuel type and cooling system on device performance. The prototype system uses 12 Peltier modules. In the initial test, the configuration of 2 modules was connected in parallel and 10 modules were connected in series using leaf fuel. Then the Peltier modules were arranged in a full series configuration. The initial test only produced a voltage of 8.1 V at a temperature difference of 80°C. This voltage is considered suboptimal, the system managed to produce a voltage of up to 30 V at a temperature difference of 104°C. This high voltage is then stabilized to 15 V using a linear regulator circuit IC 7815 assisted by a transistor and a 2N3055 capacitor, to maintain output stability before entering the solar charge controller (SCC). The SCC regulates the charging of a 12 V battery, which is then used to supply power to a 500 W inverter to power a 40 W AC lamp. The system is also equipped with an ESP32 microcontroller as a control center, as well as various sensors (current, voltage, temperature) and a 16x2 LCD to display data in real-time. This research shows that the system can efficiently generate electricity from waste incineration and has the potential to be implemented as a small-scale alternative energy solution at Politeknik Bosowa.